Transient rise in His‐lead threshold due to acute myocardial infarction. Issue 6 (15th February 2019) - Hall, Robert; Jones, Daniel A; Muthumala, Amal; Weerackody, Roshan; Sohaib, Afzal; Monkhouse, Christopher
Abstract: An 85‐year‐old male was admitted to our center with a non‐ST elevation myocardial infarction. The patient had a dual‐chamber pacemaker in situ with an atrial and His lead. A transient increase in His threshold and loss of nonselective capture occurred at the presentation of right coronary artery infarction, peaking during rotational atherectomy therapy causing loss of capture and complete atrioventricular block. A follow‐up interrogation, 2 weeks postrevascularization, showed a return to a normal nonselective capture morphology and threshold measurements. Physicians should be aware of this complication in patients with His leads, particularly those with a history of coronary artery disease.